ETHNOVETERINARY APPLICATION OF MORINDA CITRIFOLIA FRUIT PUREE ON A COMMERCIAL HEIFER REARING FACILITY WITH ENDEMIC SALMONELLOSIS - Brooks, Victoria J.; De Wolfe, Travis J.; Paulus, Tiffany J.; Xu, Jin; Cai, Jun; Keuler, Nicholas S.; Godbee, Richard G.; Peek, Simon F.; McGuirk, Sheila M.; Darien, Benjamin J. (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
Abstract We have previously reported that Morinda citrifolia (noni) puree modulates neonatal calves developmental maturation of the innate and adaptive immune system. In this study, the effect of noni puree on respiratory and gastrointestinal (GI), health in preweaned dairy calves on a farm with endemic salmonellosis was examined. Two clinical trials were conducted whereby each trial evaluated one processing technique of noni puree. Trials 1 and 2 tested noni versions A and B, respectively. Puree analysis and trial methods were identical to each other, with the calf as the experimental unit. Calves were designated to 1 of 3 treatment groups in each trial and received either: 0, 15 or 30 mL every 12 hr of noni supplement for the first 3 weeks of life. Health scores, weaning age, weight gain from admission to weaning, and weaned by 6 weeks, were used as clinical endpoints for statistical analysis. In trial 1, calves supplemented with 15 mL noni puree of version A every 12 hr had a higher probability of being weaned by 6 weeks of age than control calves (P = 0.04). In trial 2, calves receiving 30 mL of version B every 12 hr had a 54.5% reduction in total medical treatments by 42 days of age when compared to controls (P = 0.02). There was a trend in reduced respiratory (61%), and GI (52%) medical treatments per calf when compared to controls (P = 0.06 and 0.08, respectively). There were no differences in weight gain or mortality for any treatment group in either trial.